Pseudomonas cepacia: a new pathogen in patients with cystic fibrosis referred to a large centre in the United Kingdom. Issue 8 (August 1990) - Simmonds, E J; Conway, S P; Ghoneim, A T; Ross, H; Littlewood, J M
Abstract : Pseudomonas cepacia infection has become increasingly common among patients with cystic fibrosis in North America. In a large cystic fibrosis centre in the United Kingdom 11 cases have been identified during the last six years, with a maximum prevalence of 7% in 1988. Three patients have died, two of whom deteriorated rapidly shortly after acquisition of the organism despite intensive treatment with appropriate antibiotics. Analysis of possible causes of the increase in P cepacia infection suggested that neither patient to patient transmission nor the use of nebulised antibiotics was associated with an increased risk of infection.